Epidemiological profile of patients with oral alterations during the COVID-19 infection – an integrative review (Research, Society and Development, 2025)
COVID-19, first identified in Wuhan, China, in December 2019, rapidly escalated into a global pandemic, causing significant health and economic crises. In addition to systemic symptoms, several oral manifestations have been reported in infected patients, given the high presence of the SARS-CoV-2 receptor (ACE-2) in oral tissues. This study aimed to conduct an integrative literature review to analyze oral alterations associated with COVID-19, compiling cases from the PubMed database up to February 26, 2021. A total of 19 studies encompassing 266 patients were included. The most common oral manifestations were dysgeusia, ageusia, hypogeusia, aphthous and hemorrhagic ulcers, burning sensation, and xerostomia. Oral co-infections, such as herpes simplex and candidiasis, were also observed. Results indicate that patients with systemic conditions (e.g., hypertension, diabetes, obesity) tend to develop more severe symptoms and require hospitalization, particularly individuals over 60 years old. The study highlights the importance of dental professionals in the multidisciplinary management of COVID-19 patients, as oral symptoms may serve as early indicators of infection. Standardization of data reporting in future studies is essential to enhance the understanding of oral involvement in COVID-19.